Precession modulates the poleward expansion of atmospheric circulation to the Arctic Ocean - Yi Zhong; Zhengyao Lu; Stefanie Kaboth-Bahr; Jimin Yu; Keiji Horikawa; Mark J. Dekkers; Juan C. Larrasoaña; Peter D. Clift; Michael E. Weber; Flor Vermassen; Sev Kender; Chijun Sun; et al. (Nature Communications)
Abstract Under sustained global warming, Arctic climate is projected to become more responsive to changes in North Pacific meridional heat transport as a result of teleconnections between low and high latitudes, but the underlying mechanisms remain poorly understood. Here, we reconstruct subarctic humidity changes over the past 400 kyr to investigate the role of low-to-high latitude interactions in regulating Arctic hydroclimate. Our reconstruction is based on precipitation-driven sediment input variations in the Subarctic North Pacific (SANP), which reveal a strong precessional cycle in subarctic humidity under the relatively low eccentricity variations that dominated the past four glacial-interglacial cycles. Combined with climate model simulations, we highlight that precession drives meridional shifts in the northern rim of the North Pacific Subtropical Gyre (NPSG) and modulates the efficiency of heat and water vapor transfer to the SANP and Arctic regions. Our findings suggest that projections of a northward shift of the NPSG in response to future global warming will lead to wetter conditions in the Arctic Ocean and enhanced sea-ice loss.